Ct radiomic features of pancreatic neuroendocrine neoplasms (panNEN) are robust against delineation uncertainty. (January 2019) - Mori, Martina; Benedetti, Giulia; Partelli, Stefano; Sini, Carla; Andreasi, Valentina; Broggi, Sara; Barbera, Maurizio; Cattaneo, Giovanni M.; Muffatti, Francesca; Panzeri, Marta; Falconi, Massimo; Fiorino, Claudio; et al.
Highlights: The impact of delineation uncertainty on CT features (RF) was quantified for panNEN. Data of 31 patients and 3 radiologists referred to 69 RF were analyzed. Volume agreement was good (DICE: 0.78) despite the small values (median: 1.3 cc). Intra-Class Correlation (ICC) showed very high agreement (ICC > 0.8) for 65/69 RF. CT radiomics of panNEN is very robust with respect to delineation uncertainty. Abstract: Purpose: The aim of this study was to quantify the impact of CT delineation uncertainty of pancreatic neuroendocrine neoplasms (panNEN) on Radiomic features (RF). Methods: Thirty-one previously operated patients were considered. Three expert radiologists contoured panNEN lesions on pre-surgical high-resolution contrast-enhanced CT images and contours were transferred onto pre-contrast CT. Volume agreement was quantified by the DICE index. After images resampling and re-binning, 69 RF were extracted and the impact of inter-observer variability was assessed by Intra-Class Correlation (ICC): ICC > 0.80 was considered as a threshold for "very high" inter-observer agreement. Results: The median volume was 1.3 cc (range: 0.2–110 cc); a satisfactory inter-observer volume agreement was found (mean DICE = 0.78). Only 4 RF showed ICC < 0.80 (0.48–0.73), including asphericity and three RFs (of five) of the neighborhood intensity difference matrix (NID). Conclusions: The impact of inter-observer variability in delineating panNEN on RF was minimum, with the exception of the NID family and asphericity, showing a moderate agreement. These results support the feasibility of studies aiming to assess CT radiomic biomarkers for panNEN.